Compartmental syndrome and measurement of intra-abdominal pressure: the knowledge of the nurse - Gleidson Monteiro dos Santos; Ana Carolina Bezerra de Lima; Júlia Larissa de Souza Silva; Bruno Albuquerque Campos; Rita de Cássia Lira da Silva; Vania Chagas da Costa; Emanuela Batista Ferreira e Pereira (Universidade de Pernambuco, 2019)
Objective: The aim of this study was to investigate the knowledge of nurses about abdominal compartment syndrome and the measurement of intra-abdominal pressure (PIA). Methods: Descriptive research developed in intensive care units located in the municipality of Caruaru-PE. Data were collected using a semi-structured form applied to 28 nurses. Results: It was found that the professionals approached constitute a qualified team in the municipality. However, there were significant differences between them regarding the understanding of the pathology, diagnosis and execution of the technique of measurement of abdominal pressure levels. Conclusion: It was evident that the subject is not usually covered in undergraduate and / or postgraduate courses, and has low prevalence in the experience of professionals addressed, which highlights the need for investment and knowledge production about the pathology, since professional training.